Spatial re-establishment dynamics of local populations of vectors of Chagas disease. - Heinrich Zu Dohna; María C Cecere; Ricardo E Gürtler; Uriel Kitron; Joel E Cohen (Public Library of Science (PLoS), 2009)
Prevention of Chagas disease depends mainly on control of the insect vectors that transmit infection. Unfortunately, the vectors have been resurgent in some areas. It is important to understand the dynamics of reinfestation where it occurs. Here we show how continuous- and discrete-time models fitted to patch-level infestation states can elucidate different aspects of re-establishment. Triatoma infestans, the main vector of Chagas disease, reinfested sites in three villages in northwest Argentina after community-wide insecticide spraying in October 1992.Different methods of estimating the probabilities of bug establishment on each site were compared. The results confirmed previous results showing a 6-month time lag between detection of a new infestation and dispersal events. The analysis showed that more new bug populations become established from May to November than from November to May. This seasonal increase in bug establishment coincides with a seasonal increase in dispersal distance. In the fitted models, the probability of new bug establishment increases with increasing time since last detected infestation.These effects of season and previous infestation on bug establishment challenge our current understanding of T. infestans ecology and highlight important gaps in knowledge. Experiments necessary to close these gaps are discussed.